The Equal Pay Act 1972: Back to the Future? - Coleman, M (Victoria University of Wellington Law Review, 1997)
This article takes a fresh look at the Equal Pay Act 1972. Despite problems with the Court's interpretation of the Act, both during the implementation phase and more latterly in the 1986 Clerical Union decision, the article argues that equal pay for work of equal value cases can be taken under it.